2013
DOI: 10.1007/s11481-013-9447-7
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of Neurotrophic Factors by Cinnamon and its Metabolite Sodium Benzoate: Therapeutic Implications for Neurodegenerative Disorders

Abstract: This study underlines the importance of cinnamon, a widely-used food spice and flavoring material, and its metabolite sodium benzoate (NaB), a widely-used food preservative and a FDA-approved drug against urea cycle disorders in humans, in increasing the levels of neurotrophic factors [e.g., brain-derived neurotrophic factor (BDNF) and neurotrophin-3 (NT-3)] in the CNS. NaB, but not sodium formate (NaFO), dose-dependently induced the expression of BDNF and NT-3 in primary human neurons and astrocytes. Interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
107
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(109 citation statements)
references
References 35 publications
(64 reference statements)
1
107
1
Order By: Relevance
“…This strategy may include an inhibition of DAO and an increase in benzoate levels. Interestingly, oral administration of cinnamon increases the serum level of sodium benzoate in mice (11) and consumption of cinnamon lowers blood glucose levels in patients with T2DM (12). These findings further support the idea that reducing b-hydroxypyruvate levels is a worthwhile and testable strategy to restore pancreatic function and glycemic control in patients with T2DM.…”
supporting
confidence: 56%
“…This strategy may include an inhibition of DAO and an increase in benzoate levels. Interestingly, oral administration of cinnamon increases the serum level of sodium benzoate in mice (11) and consumption of cinnamon lowers blood glucose levels in patients with T2DM (12). These findings further support the idea that reducing b-hydroxypyruvate levels is a worthwhile and testable strategy to restore pancreatic function and glycemic control in patients with T2DM.…”
supporting
confidence: 56%
“…Chinese cinnamon ( Cinnamonum cassia ) and original Ceylon cinnamon ( Cinnamonum verum or Cinnamonum zylencum ) are two major types of cinnamon that are available in the US. Recently by mass spectrometric analysis, we have found that Cinnamonum verum is much more pure than Cinnamonum cassia (Jana et al 2013). Although cinnamaldehyde is present as the major peak in both Cinnamonum cassia and Cinnamonum verum , Cinnamonum cassia contains more styrene, benzene, 1,1′-(2-butene-1,4-diyl) bis-, benzene, 1,1′-(1,2-cyclobutanediyl) bis-, palmitic acid, stearic acid, 4-phenylbutyl chloride, and (2,3-diphenylcyclopropyl) methyl phenyl sulfoxide than Cinnamonum verum (Jana et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…In the liver, this cinnamic acid is β-oxidized to benzoate (Abd El-Mawla et al 2001) that exists as sodium salt (NaB) or benzoyl-CoA. Recently we have demonstrated that oral administration of ground cinnamon increases the level of NaB in serum and brain of mice (Jana et al 2013). It has been also reported that minor amount of NaB is also excreted in the urine of human (Bridges et al 1970; Kubota and Ishizaki 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, obtaining the right kind of cinnamon free of coumarin is important for long-term uptake, which is sometimes a challenge. Moreover, whole cinnamon powder contains numerous compounds and some of these compounds [styrene; benzene, 1,1′-(2-butene-1,4-diyl)bis-; benzene, 1,1′-(1,2-cyclobutanediyl)bis-; 4-phenylbutyl chloride; (2,3-diphenylcyclopropyl)methyl phenyl sulfoxide] (53) may not be beneficial. Therefore, identification of the active ingredient of cinnamon capable of recapitulating beneficial effects of cinnamon is an important step.…”
Section: Discussionmentioning
confidence: 99%